Peran Bank Desa Samirono Desa Gogik sebagai Badan Usaha Milik Desa dalam Pembangunan Ekonomi Masyarakat - wijayanti, emi; ., warsito; astuti, puji (Journal of Politic and Government Studies, 2016)
This research entitled The Role of Samirono Region Bank in Gogik Village as Region Owned Enterpreneur in Building Society Economy took the research location in a Region Bank which is located in Gogik Village, West Ungaran Sub-district, Semarang Regency. Aim of this research was to see how large was the role of region economy institution formed as Bank in assisting encouraging a regional economy building and increasing, also to give description the success of regional economy building through regional institution devdelopment mechanism. Method which was used in this research was qualitative research method. In this research, proccess of data collection was done by monitoring, interview, documentation, and literary study. Theory which was used in this research was Regional Building Theory which was related to Regional Economy Building Theory. Regional Building Theory which was used was Regional Building concept theory started from society’s changing by Rogers, this theory emphasized strategy to reach Regional Economy Building through Regional Institution development or Modernism strategy. In this research was also used economy growth theory by Harrod-Domar which explained that the success of an effort for society economy building could be seen from amount of savings percentage whichwas done by that people. The creation of regional monetary institution based on Bank in its practice gave large impact for society economy building. This was caused of Samirono Bank Regional in its operational proccess could act as work relation pattern regulator for regional economy actors, power collector for mobilizing resource to encourage economy growth maximumly, the regulator of regional economy building current information, regional consultative institution became an institution which gave general manual for people about great social economy activity pattern. The success of economy building strategy which has been done by Samirana Regional Bank was proven by total Gogik Village people’s savings asset which increased continuously. Society economy building by methods of forming regional monetary institution formed as Bank was proven could be an new mode alternatives for regional building effort. This was caused of Regional Bank succeeded to give monetary assurance and capital for regional people so that people could separate from savings and loans institution which was unhealthy so that could develop economy activity well.Keywords: Regional Economy Building, Regional Bank Institutional.